Lunar Crescent Visibility Criteria in Determining the New Islamic Month in Malaysia - Mualimin Mochammad Sahid; Habibullah Habibullah; Abdul Rahman Cemda; Mario Kasduri (Universitas Muhammadiyah Sumatera Utara in collaboration with FOFASU, 2024)
Non-Indexed Publication